2014
DOI: 10.1007/s00268-014-2722-9
|View full text |Cite
|
Sign up to set email alerts
|

Primary Fascial Closure With Laparoscopic Ventral Hernia Repair: Systematic Review

Abstract: Laparoscopic ventral hernia repair (LVHR) has grown in popularity. Typically, this procedure is performed with a mesh bridge technique that results in high rates of seroma, eventration (bulging), and patient dissatisfaction. In an effort to avoid these complications, there is growing interest in the role of laparoscopic primary fascial closure with intraperitoneal mesh placement. This systematic review evaluated the outcomes of closure of the central defect during LVHR. A literature search of PubMed, Cochrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(63 citation statements)
references
References 45 publications
0
62
1
Order By: Relevance
“…Adhesiolysis lengthens the duration of operation [8] and this has been observed also in our series as average operative time in LA and HA groups were 128 and 134 min respectively. Contrary to the findings of several previous studies [13,16,26,27] , the incidence of seroma was not lower after hybrid operations. A similar result was also seen in a recent study [25] .…”
Section: Discussioncontrasting
confidence: 57%
“…Adhesiolysis lengthens the duration of operation [8] and this has been observed also in our series as average operative time in LA and HA groups were 128 and 134 min respectively. Contrary to the findings of several previous studies [13,16,26,27] , the incidence of seroma was not lower after hybrid operations. A similar result was also seen in a recent study [25] .…”
Section: Discussioncontrasting
confidence: 57%
“…Primary closing of the defect appears increasingly to be a necessary complement in diminishing postoperative complications both short and long term [9]. A systematic review by Nguyen et al [18] comprising of 11 studies on primary closure with laparoscopic ventral repair suggested improved abdominal wall function compared to the standard bridging repair. This is based on recreating a dynamic abdominal wall with eliminating dead space.…”
Section: Discussionmentioning
confidence: 99%
“…The extracorporeal technique consists of placing multiple stab wounds on either side of the defect to pass the suture material and take interrupted stitches [16] . This may increase the risk of suture granuloma, infection or cosmetic dissatisfaction [17] . We prefer to suture the defect intracorporeally with the knots placed extracorporeally at the two ends.…”
Section: Discussionmentioning
confidence: 99%